2003
DOI: 10.1021/ja030120h
|View full text |Cite
|
Sign up to set email alerts
|

The First Experimental Test of the Hypothesis that Enzymes Have Evolved To Enhance Hydrogen Tunneling

Abstract: The literature hypothesis that "the optimization of enzyme catalysis may entail the evolutionary implementation of chemical strategies that increase the probability of quantum-mechanical tunneling" is experimentally tested herein for the first time. The system employed is the key to being able to provide this first experimental test of the "enhanced hydrogen tunneling" hypothesis, one that requires a comparison of the three criteria diagnostic of tunneling (vide infra) for the same, or nearly the same, reactio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
78
1

Year Published

2006
2006
2011
2011

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 96 publications
(82 citation statements)
references
References 71 publications
3
78
1
Order By: Relevance
“…The aggregate data for SLO-1 that include huge primary deuterium kinetic isotope effects for WT-enzyme and all mutants studied thus far, an unexpectedly small temperature dependence of the size of the isotope effects with WT-enzyme, and highly temperature dependent KIEs for the distal mutations at position 553 provide some of the strongest evidence in support of a full tunneling process in an enzyme reaction. Whereas the importance of hydrogen tunneling has increasingly achieved wide acceptance, a discussion has ensued regarding the extent to which enzymes catalyze the tunneling event, i.e., whether it may be expected that the extent of tunneling will be the same or different in relation to a comparable reaction in solution (29)(30)(31). One approach to address this question is to study the properties of a model reaction in solution.…”
Section: Distinguishing the Types Of Heavy Atom Motions That Impact H-mentioning
confidence: 99%
“…The aggregate data for SLO-1 that include huge primary deuterium kinetic isotope effects for WT-enzyme and all mutants studied thus far, an unexpectedly small temperature dependence of the size of the isotope effects with WT-enzyme, and highly temperature dependent KIEs for the distal mutations at position 553 provide some of the strongest evidence in support of a full tunneling process in an enzyme reaction. Whereas the importance of hydrogen tunneling has increasingly achieved wide acceptance, a discussion has ensued regarding the extent to which enzymes catalyze the tunneling event, i.e., whether it may be expected that the extent of tunneling will be the same or different in relation to a comparable reaction in solution (29)(30)(31). One approach to address this question is to study the properties of a model reaction in solution.…”
Section: Distinguishing the Types Of Heavy Atom Motions That Impact H-mentioning
confidence: 99%
“…Although it is now becoming widely accepted that hydron tunnelling does indeed occur in some of these enzymes (e.g. Ball 2004;Liang & Klinman 2004), it is not clear how widespread it is, or how important the phenomenon may be to catalysis (Bahnson et al 1997;Doll et al 2003;Warshel 2003). To contribute to this discussion, we have studied the enzyme methylamine dehydrogenase (MADH,EC 1.4.99.3) with the aim of understanding its structural features which promote or enhance the tunnelling mechanism.…”
Section: Introductionmentioning
confidence: 99%
“…Although tantalizing, the relatively small difference in the observed KIEs is not sufficient to conclude that there is a greater tunneling contribution in the enzymatic process than that of the uncatalyzed reaction in water. A number of experimental and theoretical studies suggested that the extent of tunneling was the same in several enzymes as in model reactions in solution (2,9,10), whereas other experiments showing differential tunneling behaviors may be attributed to different reaction mechanisms (2,(11)(12)(13). Nuclear tunneling cannot be measured directly, and the best experimental diagnostic of tunneling is through measurement of kinetic isotope effects (14).…”
mentioning
confidence: 99%